Seawater Intrusion Inhibits Nitrate Removal in Tidal Marsh Aquifers - Zhaoyang Luo; Jun Kong; Xiayang Yu; Chao Gao; D. A. Barry; Simone Fatichi (Water Resources Research)
Abstract Tidal freshwater marshes are threatened by seawater intrusion globally due to freshwater discharge reduction and sea‐level rise. However, terrestrial nitrate (NO3−) transport responding to seawater intrusion remains poorly understood in tidal marshes. After validation against laboratory experiments, numerical simulations were conducted to analyze seawater intrusion effects on terrestrial NO3− transport and transformation in tidal marsh aquifers. Results reveal that seawater intrusion noticeably affects NO3− transport from the marsh aquifer to the tidal creek. Seawater intrusion results in an upper saline plume and a saltwater wedge within the aquifer, which markedly narrows the discharge outlet width of the NO3− plume and intensifies the peak NO3− flux across the creek bank. Consequently, both the NO3− removal efficiency and total nitrogen gas load to the creek decrease substantially after seawater intrusion. This is because the reduction of the transit time and the mixing zone width of the NO3− plume after seawater intrusion weakens denitrification. Sensitivity analyses indicate that the difference of the NO3− removal efficiency before and after seawater intrusion depends on soil properties. A larger unsaturated flow effect, saturated hydraulic conductivity or effective porosity leads to a greater difference of the NO3− removal efficiency before and after seawater intrusion. The predicted decrease of the NO3− removal efficiency after seawater intrusion is consistent with existing field data.